Kinetics of ofloxacin and its metabolites in cerebrospinal fluid after a single intravenous infusion of 400 milligrams of ofloxacin. - Nau, R (1994)
Ofloxacin has been reported to diffuse readily into the cerebrospinal fluid (CSF) in subjects with both inflamed and uninflamed meninges. However, with moderately susceptible bacteria, ofloxacin concentrations in CSF may be subtherapeutic after administration of an intravenous (i.v.) dose of 200 mg. For this reason, the kinetics of a higher dose of ofloxacin in CSF was studied with humans. Six patients with occlusive hydrocephalus caused by cerebrovascular diseases who had undergone external ventriculostomy received 400 mg of ofloxacin i.v. over 30 min. Serum and CSF samples were drawn repeatedly. Serum from 12 healthy volunteers was sampled repeatedly after they had received 400 mg of ofloxacin i.v. over 60 min. Ofloxacin, ofloxacin-N-oxide, and N-desmethyl-ofloxacin concentrations were determined by high-pressure liquid chromatography with fluorescence detection. The maximum ofloxacin concentrations in the serum of the patients ranged from 7.36 to 11.6 mg/liter (mean, 9.55 mg/liter), the apparent volume of distribution/body weight was 0.96 to 1.19 liters/kg (mean, 1.11 liters/kg), and the total body clearance was 115 to 280 ml/min (mean, 192 ml/min). In healthy volunteers, the volume of distribution/body weight and the total body clearance were higher and amounted to 1.27 +/- 0.18 liters/kg and 217 +/- 43 ml/min (means +/- standard deviations), respectively. These differences were attributed to the older ages of the patients than the volunteers. In the CSF of patients, maximum concentrations of 1.00 to 2.85 mg/liter (mean, 2.04 mg/liter) were observed 0.5 to 4 h following the completion of the ofloxacin infusion. Ofloxacin elimination from CSF was slightly slower than that from serum (half-lives, 4.33 to 10.02 versus 4.27 to 9.14 h). The overall penetration of ofloxacin into CSF, as expressed by the ratios of the areas under the concentration-curves, amounted to 0.59 to 0.81 (mean, 0.65). The more hydrophilic metabolites ofloxacin-N-oxide and N-desmethyl-ofloxacin passed less readily than ofloxacin into the CSF. In conclusion, the concentrations in CSF attained after a single i.v. infusion of 400 mg of ofloxacin in the absence of meningeal inflammation appear to be high enough to inhibit the growth of most staphylococci and members of the family Enterobacteriaceae, which are often involved in CSF shunt infection. Yet, in view of pharmacodynamic studies suggesting a peak concentration in CSF of at least 10-fold the MIC, the use of ofloxacin for central nervous systems infections is optimal only with highly susceptible pathogens (MIC, less than or equal to 0.12 mg/liter).